STUDI KOMPARATIF PRODUKTIVITAS DAN PENDAPATAN USAHATANI KOPI DENGAN CARA SAMBUNG PUCUK DAN CARA INDUKAN DI KECAMATAN KOTA AGUNG KABUPATEN LAHAT - Herlangga, Pebi; Batubara, Mustopa Marli; Kurniawan, Rahmat (Muhammadiyah University of Palembang, 2016)
The purpose of this study was to determine how much a comparison of productivity of land, labor , and capital in coffee farming by means of grafting and how broodstock in District Kota Agung Lahat and to determine the difference coffee farm income by way of grafting and how broodstock in the district of Kota Agung Lahat. This research was conducted in the district of Kota Agung Lahat . In April to June 2016. The research method used was a survey , for the sampling method used was stratified random sampling . Stratified random sampling is a sampling of a random member of the population stratification ( grouping ) . Data collection methods used in this study is the observation and direct interview to the respondents who have been determined by using tools such as quisoner that has been prepared in advance . Tabulation data processing is done then analyzed by descriptive qualitative approach and descriptive analysis with mathematical approach. The results showed that , productivity of land, labor and capital in coffee farming by means of grafting significantly different when compared with the productivity of land , labor and capital in coffee farming by means of sires per hectare per year. As well as income on a coffee farm that use grafting significantly different when compared to coffee farming by means of sires per hectare per year.